Pengaruh Implementasi Good Corporate Governance terhadap Permodalan dan Kinerja Perbankan Di Indonesia: Manajemen Risiko Sebagai Variabel Intervening - Permatasari, Ika; Novitasary, Retno (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82)DO - 10.24843/JEKT.2014.v07.i01.p06)
Regulation of Bank Indonesia No. 8/4/PBI/2006 as amended by regulation No. 8/14/2006 about implementation of corporate governance become be a proof why corporate governance important in the banking sector. The purpose of this study was to determine the influence of corporate governance on risk management, bank capital, and bank performance in Indonesia.  Implementation on corporate governance is measured by a composit score of corporate governance which is the result of bank self assessment. Risk management is measured by Non Performing Loans (NPL). Bank capital is measured by Capital Adequacy Ratio (CAR) and bank performance is measured by Return On Equity (ROE). The result showed that corporate governance affect risk management, corporate governance and risk management does not affect bank capital, and corporate governance do not affect bank performance, but risk management affect bank performance. Thus the risk management can be an intervening variable between corporate governance and bank performance.
Keywords: composite score , good corporate governance , NPL , CAR , ROE